1978
DOI: 10.1007/bf00643222
|View full text |Cite
|
Sign up to set email alerts
|

l-Alanine as an end product of glycolysis inSaccharomyces cerevisiae growing under different hypoxic conditions

Abstract: Saccharomyces cerevisiae growing under anaerobic or other hypoxic conditions releases L-alanine into the culture medium as an end product of glycolysis. Although the production of alanine is not as high as that of other fermentation products (ethanol, glycerol, succinic acid), consideration of the pathways leading to alanine in fermenting yeasts indicates that the release of alanine is advantageous to the cellular economy and may be considered as a safety device for excreting reducing equivalents derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The presence of at least two alanine aminotransferase isozymes is widely distributed in animals, plants, yeasts and bacteria. In these systems, ALT isozymes have been considered to constitute the main pathway leading to alanine biosynthesis and catabolism [1][6]. Alanine catabolic and anabolic pathways are central in nitrogen and carbon metabolic networks.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of at least two alanine aminotransferase isozymes is widely distributed in animals, plants, yeasts and bacteria. In these systems, ALT isozymes have been considered to constitute the main pathway leading to alanine biosynthesis and catabolism [1][6]. Alanine catabolic and anabolic pathways are central in nitrogen and carbon metabolic networks.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in response to hypoxia, mammalian culture cells produce increased amounts of amino acids, fatty acids, and phospholipids, in addition to lactate (4,21), whereas Saccharomyces cerevisiae cells produce increased amounts of ethanol, glycerol, succinate, and alanine (22,23) as the end products of glycolysis. The production of pyruvate, which is associated with the synthetic pathways of fatty acids, nucleotides, and other amino acids (24), is necessary for cell growth under hypoxia.…”
mentioning
confidence: 99%
“…Alanine aminotransferases catalyse reversible transamination between alanine and α-ketoglutarate, leading to pyruvate and glutamate. At least two alanine aminotransferase isozymes, generated through independent gene duplication events, occur frequently in animals, plants, yeasts and bacteria, and are proposed to be involved in the main pathways of both alanine biosynthesis and catabolism [15,[54][55][56][57][58]. Amino acid metabolism has been thoroughly studied in S. cerevisiae; however, no alanine auxotrophs have been isolated from this yeast.…”
Section: Modelling Of the Nrg1/rtg3 Complex The Unicity Of Nrg1mentioning
confidence: 99%
“…ALT1 and ALT2 encode proteins with 65% identity and are assumed to be paralogous alanine transaminases [ 15 ]. Additional phylogenetic studies suggested that ALT1 and ALT2 originated in one of the two distinct parental strains, which gave rise to the ancestral hybrid [ 16 ].…”
Section: Introductionmentioning
confidence: 99%